Adaptasi Academic Motivation Scale (AMS) versi Bahasa Indonesia - Ramadhan Dwi Marvianto; Wahyu Widhiarso (Faculty of Psychology, Universitas Gadjah Mada, 2018)
This study aimed to adapt the Academic Motivation Scale (AMS) into Indonesian language. Data collection was done using online survey to 617 high school students in Yogyakarta. The analyzed property included discrimination indices, mean, and standard deviation for item level. At test level, the analyzed property were validity and reliability. Procedure of adaptation performed following adequate adaptation guidelines. Findings on the psychometric property evaluation showed that adapted AMS had satisfactory discriminating indices, mean, and standard deviation of items. At the test level, Adapted AMS had reliability values ranging from 0.73 to 0.90. Construct validity test showed satisfactory results. This was seen from the results of inter-dimensional correlations that showed a simple pattern as in research conducted by the original scale’s maker. Thus, Indonesian version of AMS had satisfactory construct validity and produced reliable scores, so it can be used.